First course of palliative care in undergraduate medicine at a Peruvian university: Primer curso de cuidados paliativos en pregrado de medicina en una universidad peruana - Portugal-Sánchez, José (2023)
The inclusion of a palliative care course for students in the ninth semester of the professional medical career is an important step in teaching in a Latin American country, seeking to bridge the gap between curative medicine that neglects symptom control and quality of life. Allowing students to better understand the disease process and the epidemiological transition that is taking place worldwide and affects all health systems. The students' appreciations are presented regarding little-reviewed aspects such as coping with death, end of life and the patient-family relationship.